ANALISA PENGARUH AXIAL FORCE DAN ROTATIONAL SPEED PADA PROSES REPAIR AXLE SHAFT BEKAS MENGGUNAKAN FRICTION WELDING TERHADAP KETANGGUHAN AXLE SHAFT - Hartanto, Irfan Malik; Ainur Rasyid, Akhmad Hafizh (Otopro, 2020)
Increasing truck growth and a large number of failure phenomena on Axle Shaft components. Implied by an increase in shaft waste that fails, so an effort is needed to reduce it. One of the waste control methods that can be used is the repair principle. Repair is the maintenance and repair of waste that can still be used for the same function or other functions with certain businesses. The repair method carried out in this study is the process of joining the material using the friction welding process. Seeing the above phenomenon the researcher wants to know the effect of rotational speed and axial force on and toughness in the axle shaft shaft welding area. This research method uses an experimental research method with a welding process carried out on a lathe that has been added a hydraulic pressure device as an axial suppression mechanism. The results showed the greatest impact strength was found in variations of rotational speed of 1010 Rpm with the highest yield of 0.065030 J / mm² at forging pressures of 40 Kg / cm2 in weld metal areas while the lowest impact test results were generated from variations of 1800 Rpm rotational speed of 0.040970 J / mm² at forging pressure 20 Kg / cm2 in the weld metal area. So it can be concluded that rotational speed and axial pressure affect the impact strength of friction welding results